Tipo e época de poda na produção e qualidade de pêssego - Gonçalves, Michél Aldrighi (2011)
The present work aimed to evaluate and characterize the behavior of different peach genotypes submitted to variations of period and type of pruning, in the region of Pelotas, RS. The work was carried out in Pelotas, RS, in an experimental area belonging to Embrapa Clima Temperado (CPACT) during 2009 and 2010 seasons. Two experiments were done: the first one was comprised of a combination among three periods of pruning (Winter pruning WP; winter pruning plus summer pruning WSP; and summer pruning SP) and three genotypes (Cascata 805, Cascata 834 (BRS Kampai) and Cascata 952 (BRS Rubimel), resulting in nine distinct combinations. The second experiment consisted in three types of pruning (short pruning SP; long pruning LP; and no shoot topping NST) and two genotypes (Riograndense and Leonense), resulting in six treatments. In general, the chemical characteristics of the fruits are not affected by the different pruning period, as well as, the fruitset. BRS Rubimel did not show uniformity of yield in the following years when using the summer pruning; however, BRS Kampai had a good yield equilibrium at all pruning date tested. Trees pruned only in the winter period showed higher vigor whether compared to other studies. The different types of pruning directly affected the number of flowers and fruits, diameter and mean mass, and yield. The short pruning stimulates the growth of undesirable shoots, making unviable the summer pruning practice. In general, the variations of pruning type and period could be commercially used depending on the genotype studied.